Women's legal protection during the war in Islam and international humanitarian law - Wael Mahmoud Fakhry (Penerbit Universiti Kebangsaan Malaysia, 2024)
The goal of this study was to outline serious abuses committed against women during the war and demonstrate how the legal system handles these kinds of crimes re7lects both the regulations' inapplicability and incapacity to protect women. We attempted to review a few of those regulations, but since human made regulations cannot be compared to those created by God, the study concluded that Islamic laws protecting women ought to be implemented during times of armed con7lict due to their ef7icacy. Regarding the protection of women during con7lict or war, every Muslim is required to abide by the laws of the Quran and Hadith. Eventually, this could apply to the entire world.